ChemInform Abstract: Employing Arynes in Diels—Alder Reactions and Transition‐Metal‐Free Multicomponent Coupling and Arylation Reactions. Issue 47 (3rd November 2016) - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T.
Abstract: Review: 58 refs.